Penyuluhan dan Pendampingan Pencegahan Penyalahgunaan Narkoba Pada Pelajar di Desa Campakasari Purwakarta: Counseling and Assistance in the Prevention of Drug Abuse to Students in Campakasari Village, Purwakarta - Rosmayati, Yati (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This community service activity is motivated by the observations of researchers regarding drug abuse in students which is increasingly being found. The form of activity in this activity uses the lecture method, and counseling, where all activities are designed and carried out in non- formal situations for 30 students in each elementary school within the scope of Campakasari Village, Purwakarta. The results of the PBP implementation can increase participants’ literacy regarding drugs and efforts to prevent their abuse. This refers to the final result that compares the pre-test with the post-test, which shows an increase in knowledge where participants are able to mention various types, hazards, and prevention efforts from 30% to 90% with an average value of 82 out of 100.